Modul Berbasis Problem-Based Learning Terintegrasi Etnobotani: Upaya Meningkatkan Berpikir Kritis dan Motivasi Siswa - Suhartati Suhartati; Marlina Ummas Genisa; Wulandari Saputri (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Based on observations and interviews at SMA Negeri 1 Tempilang, biology teaching is still dominated by lecture methods (31.8%), and 50% of teachers do not understand the learning model. In fact, the Independent Curriculum emphasizes developing 21st-century skills, such as critical thinking and motivation to learn, which are not considered in existing teaching tools. This study aims to create a Problem-Based Learning (PBL)-based teaching module on biodiversity materials. The study population consisted of students of class X with a sample of classes X1 to X4. The development model uses 4D: define, design, develop, and disseminate. Data were collected through interviews, questionnaires, and observations, then analyzed with the N-Gain test—the results of the Define phase show the need for teaching modules to support critical thinking. The design phase resulted in a module design and 10 valid essential questions of thinking (reliability 0.801). At the development stage, this module was rated very well in terms of language (90.00%) and material (90.44%), as well as in terms of devices (82.70%) and ratings (82.70%). The modules are also stated by practical teachers (87.5%) and are easy for students to read (92%). Therefore, PBL-based teaching modules are suitable for improving students' critical thinking skills and motivation to learn.